Root distribution of mume rootstocks budded with ’Aurora-1’ peach - Mayer, Newton Alex; Pereira, Fernando Mendes; Barbosa, José Carlos; Koba, Valter Yoshio (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this research was to study the root distribution of three mume (Prunus mume Siebold et Zucc.) rootstocks (Clone 05, Clone 15, and Rigitano cultivar) propagated by herbaceous cuttings, in field conditions. The plants budded with 'Aurora-1' peach [Prunus persica (L.) Batsch] were carried in 6x1 m space in a Hapludalfs soil with sandy medium texture. After 34 months of transplant, two plants of each rootstock were evaluated, being demarcated 36 monoliths (0.5x0.5x0.4 m) round about of each plant, with iron bars (0.6 m) and plastic ribbons. The soil was removed with water jets until 0.4 m depth. There were no differences, among rootstocks, in fresh and dry root weight, and in thin and thick roots which showed similar distribution around the plant among rootstocks studied. Although showing no typical axial root formation, thick roots presented vertical growth, beyond 0.4 m depth, and concentrated 0.5 m around the trunk. The fine roots presented horizontal growth beyond the canopy projection and beyond the evaluated distance of 1.5 m in transversal sense to line plantation. The clones 05, 15 and Rigitano cultivar, used as mume rootstocks, show suitable peach tree anchorage.